PROBLEMATIKA PENERAPAN FORMULA PELAYANAN BERKUALITAS PADA SEKTOR PUBLIK DI INDONESIA - Sudarmo Sudarmo (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2009)
The implementation of Total Quality Management (TQM) in attempting to meet quality service in public sector in Indonesia is still problematical, mainly due to family-oriented bureaucracy behavior, incompatibility between praxis of TQM and that of public sector and practices of patrimonial management. These impedimentscan be reduced by keeping various kinds of commitments in terms of cultural changes, top management involvement totality, total quality-behavior oriented, time, and financial sources. In addition, commitment to reform the moral and ideology of the ruler and decision makers as well as their political will to materialize it is obviously required. Despite difficulties in changing organization culture, some ways offer a solution. Organization culture toward quality service can be changed by restructuring the organization, improving property rights, deploying new managers, and tightly scheduling the period of time in implementing TQM.